TEKNIK ADAPTASI POLA NAFAS TERHADAP PENURUNAN INTENSITAS NYERI DAN MEMPERLANCAR PROSES PERSALINAN - ., Suryanti; Choeriyah, Uswatun; Suparti, Ipang (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
ABSTRACT: BREATHING PATTERN ADAPTATION TECHNIQUES TO DECREASE THE INTENSITY OF PAIN AND EXPEDITE THE PROCESS LABOR. Labor pain is a natural response of the mother's body when undergoing childbirth. Pain can cause problems are increasing concerns that increased production of adrenal hormones and cause constriction of the blood vessels (vasoconstriction) which causes the blood flow to the fetus and the mother declined. Labor pain can be minimized with effective breathing exercises during labor. Models used in this study is a quasi experimental. The design of the study was cross-sectional. Adaptation research variables include breathing patterns, labor pain and delivery time. Analysis of data using independent T-test. The results showed statistically significant differences in pain intensity between the groups given maternal adaptation technique with maternal breathing pattern is not given breathing pattern adaptation techniques in maternity hospitals in Cilacap (p = 0.04 <0.05), there are significant differences between the groups at the time of delivery, maternal adaptation techniques are given breathing pattern with maternal adaptation techniques are not given breathing pattern in maternity hospitals in Cilacap (p = 0.04 <0,019). The conclusion of this research is that there is no significant difference in pain intensity and time of delivery on maternal adaptation techniques are given breathing pattern, so it is important breathing pattern adaptation techniques applied to the labor process to reduce labor pain and expedite the delivery process.Keywords: Adaptation patterns of breath, pain in labor, delivery time